2003
DOI: 10.1023/b:bebm.0000017097.75818.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Action Mechanisms of Dimebon and Memantine on AMPA- and NMDA-Subtypes Glutamate Receptors in Rat Cerebral Neurons

Abstract: Dimebon in low concentrations potentiated activity of AMPA-receptors in rat cerebellar Purkinje neurons, while memantine produced only an insignificant potentiation in a small group of these cells. In cortical neurons of rat brain memantine efficiently blocked NMDA-induced currents in dimebon-insensitive neurons. By contrast, its effect was far weaker in neurons, where the blocking action of dimebon on NMDA-receptors was most pronounced. It was hypothesized that the differences in the effects of memantine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 5 publications
3
65
0
Order By: Relevance
“…The memory-enhancing effects of dimebon may indicate simultaneous activity toward AMPA, NMDA, dopamine and serotonin receptors, all of which have been involved in inhibitory and appetitive hippocampus-dependent learning (Ungerer et al, 1998;Orsetti et al, 2001;Rogawski and Wenk, 2003;LaLumiere et al, 2003;Lynch and Gall, 2006;Balschun et al, 2006;Da Silva Costa et al, 2009;Benchenane et al, 2010). In particular, it has been hypothesised that dimebon's activity as a positive modulator of AMPA receptors and low affinity non-competitive blocker of NMDA receptors via a multi-drug mechanism, can explain the pro-cognitive action of this compound (Grigorev et al, 2003;Grigoriev 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The memory-enhancing effects of dimebon may indicate simultaneous activity toward AMPA, NMDA, dopamine and serotonin receptors, all of which have been involved in inhibitory and appetitive hippocampus-dependent learning (Ungerer et al, 1998;Orsetti et al, 2001;Rogawski and Wenk, 2003;LaLumiere et al, 2003;Lynch and Gall, 2006;Balschun et al, 2006;Da Silva Costa et al, 2009;Benchenane et al, 2010). In particular, it has been hypothesised that dimebon's activity as a positive modulator of AMPA receptors and low affinity non-competitive blocker of NMDA receptors via a multi-drug mechanism, can explain the pro-cognitive action of this compound (Grigorev et al, 2003;Grigoriev 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of dimebon against a set of biochemical targets indicated that dimebon inhibits alpha-adrenergic receptors (alpha1A, alpha1B, and alpha1D, and alpha2A, alpha 2B, and alpha 2C), histamine H1 and H2 receptors and serotonin receptors (5-HT-2A, 5-HT2B, 5-HT2C, 5-HT5A, 5-HT6, and 5-HT7), dopamine receptors (D, D2S, and D3), and imidazoline I2 receptors (Schaffhauser et al, 2009;Giorgetti et al, 2010). At low concentrations, dimebon potentiates the activity of AMPA-receptors and blocks NMDA-receptors in neurons (Grigorev et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Latrepirdine is proposed to interact with glutamate Reduces oxidative stress, reduces amyloid plaques, improves memory deficits in transgenic mouse models of AD No major effect on cognitive function [132][133][134][135][136][137][138][139] AD = Alzheimer's disease; ROS = reactive oxygen species; SOD = superoxide dismutase; MitoQ = mitoquinone mesylate; AMPK = adenosine monophosphate-activated protein kinase; NAD = nicotinamide adenine dinucleotide; SIRT1 = sirtuin 1 receptors, block voltage-dependent calcium channels, and inhibit mitochondrial permeability, thereby suppressing unnecessary mitophagy or apoptosis [153,154]. In a Phase II clinical trial in patients with moderate AD, it significantly improved cognitive function over placebo [155].…”
Section: Apoptosis and Mitophagy As Therapeutic Targetsmentioning
confidence: 99%
“…Dimebon exhibits a rich pharmacological profile and binds to histamine-, adrenergic-, dopamine-, and serotonin-receptors [25,27]. It is known to be a weak inhibitor of acetylcholinesterase (IC 50 = 8-42 µM) [24], N-methyl-Daspartate (NMDA) receptors (IC 50 = 10 µM) [25,28], and voltage-gated calcium channels (IC 50 = 50 µM) [25,29]. In addition, µM concentrations of Dimebon have previously been shown to protect against neuronal cell death induced by Aβ 25−35 [24] and to modulate the mitochondrial permeability transition pore (10-200 µM) [20].…”
Section: Introductionmentioning
confidence: 99%